A novel eco-friendly Acinetobacter strain A1-4-2 for bioremediation of aquatic pollutants - Rui Wang; Jiahua Wang; Ling Wang; Yulun Cai; Yuan Wang; Huifang Luo; Bing Chen; Junlv Chen; Jiasong Fang; Zengfu Song (Scientific Reports)
Abstract The increasing accumulation of hydrocarbons and aromatic compounds in aquatic ecosystems, stemming from anthropogenic activities, poses severe ecological challenges, including disrupting biodiversity and threatening human health through the food chain. This study presents Acinetobacter strain A1-4-2, isolated from a hairy crab farming base, which could represent a novel Acinetobacter species. The metagenomic analysis of approximately 12,000 publicly available datasets revealed that this novel Acinetobacter species is widely distributed across various environments, particularly in those with high organic matter content, such as sludge, feces, and wastewater. Strain A1-4-2 exhibited exceptional metabolic capabilities, effectively degrading a diverse range of substrates, including amino acids, organic acids, oils, n-alkanes, lignin, and aromatic monomers. Genomic analysis, coupled with biological experiments, revealed that strain A1-4-2 exhibited resistance to a very limited kind of antibiotics. Moreover, the strain’s biosafety, affirmed through zebrafish toxicity assays, underscores its suitability for environmental release. Additionally, the feasibility of genetic manipulation of strain A1-4-2 gives it the potential to become a chassis cell, enabling it to degrade organic pollutants more efficiently through genetic engineering. Our findings elucidate the strain’s genomic and metabolic attributes, offering insights into its biodegradation potentials and developing effective strategies for ecological restoration in face of pollution.